Model Victims of Hate: Victim Blaming in the Context of Islamophobic Hate Crime - Erentzen, Caroline (Journal of interpersonal violence, 2021)
Prior research has explored victim blaming in the context of hate, often depicting hate crime victims as relatively passive recipients of harassment and violence. In reality, victims often do engage with their perpetrators, and the present research explored the effect that victim behavior might have on observer reactions to Islamophobic hate crimes. Participants completed a measure of Islamophobia and read a scenario in which a White man verbally harassed a victim in the park before physically assaulting him. We manipulated both the victim’s identity (White or South Asian Muslim) and the victim’s response to the perpetrator’s verbal harassment (the victim either ignored the offensive comments, verbally reacted to them, or became physically confrontational). When the victim was portrayed as passive and nonresponding, the South Asian Muslim victim attracted lower victim blame, higher perpetrator blame, and increased certainty that the offense was a hate crime. As the victim’s behavior became more aggressive, victim blaming increased and perpetrator blaming decreased, but only for the South Asian Muslim victim. It appeared that observers scrutinized the behavior of the South Asian Muslim victim in a way they did not for the White victim, such that sympathy toward the Muslim hate crime victim was tied to his “good behavior.” We propose that observers hold expectations of the model hate crime victim, one who is a racialized, religious, or sexual minority who accepts harassment passively and with good behavior; deviation from this script results in a loss of sympathy and an increase in victim blaming. Finally, those higher in Islamophobia displayed reduced perpetrator blame, guilt, and sentences but greater victim blame when the crime targeted a South Asian Muslim as opposed to White victim.